THE USAGE OF THE ENGLISH LANGUAGE IN THE WORLD (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the global use of the English language, tracing its historical expansion through British colonialism and later U.S. influence. It describes the distribution of English across the world using Kachru’s Three Circles model and highlights its role as an international lingua franca in science, business, diplomacy, and technology. The article also discusses the impact of digital communication on the spread of English and addresses debates about linguistic inequality and cultural influence. It concludes that while English offers significant benefits for global communication, its dominance raises challenges regarding linguistic diversity.